On Religious Hypothesis - Dziobkowski, Bogdan (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
According to Professor Ryszard Kleszcz, the analytical philosophy of religion deals primarily with the problems of meaning and justification of religious beliefs. The paper shows two solutions to these problems. The first one was presented by Józef Maria Bocheński in his The Logic of Religion. On the basis of this approach, faith is an act in which a sentence with a certain content is considered true. This sentence is a hypothesis explaining all or part of an individual’s experience. Kleszcz agrees with such an answer. A similar way of perceiving religion can also be found in the papers by Jacek Jadacki and Bogusław Wolniewicz. A completely different concept of religion is presented in the early philosophy of Ludwig Wittgenstein. According to Wittgenstein, religious beliefs are nonsense. They are meaningless and have no content so there is no justification in this case. Uttering such nonsensical sentences, however, indicates a certain tendency that is inherent in human nature, i.e. a tendency to cross the borders of language and thus the borders of the world. Wittgenstein claims that religion is the attitude of the metaphysical subject towards the world. This attitude makes the world cease to be merely a mixture of facts and begin to appear as a meaningful whole.